Influence of recession on the infiltration in open furrows on slopes, under constant flow - Almeida Lima, Valéria Ingght; da Silva, Silvanete Severino; Vieira de Azevedo, Carlos Alberto; Cezar de Albuquerque Filho, João Audifax; Vieira Pordeus, Roberto (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2014)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--> <span style="font-size: 10.0pt; line-height: 150%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">During surface irrigation, some phases related to its hydraulics are produced. The monitoring of these phases allows determining dvance and recession curves. The recession phase occurs after the application of water to furrows. Hydraulically, it is the most complex phase and therefore difficult to predict in mathematical treatments. To obtain the recession phase, it is necessary to determine the time at which water advances over the soil surface to specific points, called stations, over the area and then record the time at which it disappears. Observing the passage of the recessive front through the measuring stations along the furrows as a function of time defines the recession curve. Using field data obtained by Ramsey (1976) and by the Department of Agriculture and Chemical Engineering, University of Colorado (1980), <span style="font-size: 10.0pt; line-height: 150%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: PT-BR; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;">in three different farms: Horticulture, Stieben e Benson. T<span style="font-size: 10.0pt; line-height: 150%; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="EN-US">his work aimed to study the effect of the recession time on the infiltrated profile in surface irrigation. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->